Digital Lifestyle Transformation: Implications on Physical Activity and Health of Modern Communities in Medan Province - Restu Auliani; Nelson Tanjung; Risnawati Tanjung; Erba Kalo Manik (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The development of digital technology in Medan Province has fundamentally changed people's behavior with increased use of smartphones, tablets, and computers. This study aims to evaluate the empirical relationship between duration of digital device use, physical activity level, and physical and mental health of 18-45 year olds in Medan. Through an online survey of at least 500 respondents recruited by random sampling, data was analyzed using descriptive statistics, Pearson correlation, and linear regression to test hypotheses regarding the influence of digital use on fitness. The results showed a negative correlation between high screen time and physical activity, as well as potential risks of musculoskeletal, sleep disorders, increased BMI, stress and anxiety in intensive users. In contrast, individuals who regularly engaged in ?150 minutes of physical activity per week reported better feelings of health and psychological well-being. These findings confirm the urgency of education-based interventions, digital wellness regulation, and physical activity promotion as strategies to mitigate the negative impacts of digitalization on public health. Recommendations include public health policy programs, integration of healthy lifestyle support technologies, and healthy digital awareness campaigns among Medan residents.